Pengembangan model pembelajaran prakarya dan kewirausahaan dengan prinsip the great young entrepreneur di SMK untuk Kurikulum 2013 - Catarina Wahyu Dyah Purbaningrum; Soenarto Soenarto (Jurnal Pendidikan Vokasi, 2016)
Penelitian ini bertujuan: (1) menghasilkan model pembelajaran prakarya dan kewirausahaan  dengan prinsip "The Great Young Entrepreneur" di SMK untuk kurikulum 2013; (2) menghasilkan perangkat pembelajaran prakarya dan kewirausahaan di SMK untuk kurikulum 2013 yang dapat menumbuhkan mental dan motivasi peserta didik untuk berwirausaha; (3) mengetahui tingkat kepraktisan model pembelajaran prakarya dan kewirausahaan dengan prinsip The Great Young Entrepeneur yang telah dikembangkan; dan (4) mengetahui tingkat keefektifan model pembelajaran prakarya dan kewirausahaan dengan prinsip The Great Young Entrepreneur yang telah dikembangkan. Hasil penelitian adalah sebagai berikut: (1) Model pembelajaran prakarya dan kewirausahaan dengan prinsip The Great Young Entrepreneur dapat digunakan dengan baik.(2) Perangkat pembelajaran yang dihasilkan yaitu: buku panduan model dan materi ajar. (3) Model pembelajaran prakarya dan kewirausahaan dengan prinsip TGYE dan perangkat pembelajaran berdasarkan hasil ujicoba memenuhi kriteria praktis.(4) Model pembelajaran prakarya dan kewirausahaan dengan prinsip TGYE dan perangkat pembelajaran memenuhi kriteria efektif. DEVELOPING A CRAFT AND ENTREPRENEURIAL LEARNING MODEL WITH THE PRINCIPLE OF "THE GREAT YOUNG ENTREPRENEUR" AT SMK FOR CURRICULUM 2013 Abstract The purposes of this study were (1) to produce a craft and entrepreneurship learning model with the principle of "The Great Young Entrepreneur" at SMK's for curriculum in 2013; (2) produce craft and entrepreneurial learning tools at SMK for curriculum 2013 that can grow mental and motivation of learners to be an entrepreneur; (3) determine the level of practicality of the learning model with the principle of "The Great Young Entrepreneur which was developed; and (4) determine the level of effectiveness of the learning model with the principle of the great young entrepreneur which was developed. The results of the study are as follows (1) Craft and entrepreneurial learning model with the principle "The Great Young Entrepreneur" can be used (starting from the beginning of the formatiom of groups up to business assistance through "The Great Young Entrepreneur" Community). (2) learning device resulting from the development of craft and entrepreneurial learning model with "The Great Young Entrepreneur" principle is guide book model and teaching materials. (3) craft and entrepreneurial learning model with "The Great Young Entreprenuer" principle and learning device based on the results meet the practicality criteria. (4) craft and entrepreneurial learning model with "The Great Young Entrepeneur" principle and learning device based on the results meet the criteria of effectiveness.